End-of-Life Plans for African American Older Adults With Dementia. (October 2018) - Moss, Karen O.; Deutsch, Nancy L.; Hollen, Patricia J.; Rovnyak, Virginia G.; Williams, Ishan C.; Rose, Karen M.
African Americans are perceived to be least likely of all racial and ethnic groups to prepare for the end of life. However, verbal plans for the end of life are of particular importance to this population and may help understand why they are less likely to possess a formal end-of-life care planning document. The purpose of this study was to determine the number of formal and/or informal end-of-life care plans that existed among a convenience sample of African American older adults with dementia. For this descriptive study, data were collected from African American family caregivers (N = 65) of older adults with dementia. Descriptive statistics were conducted. Caregivers in this sample reported high rates of formal and/or informal end-of-life plans for their care recipients. Agency forms (power of attorney, health-care surrogate, or guardianship forms) had been obtained by 74% of the care recipients, while 63% of them possessed a formal end-of-life care planning document. All combined, 88% of the caregivers possessed at least 1 document or verbal information concerning end-of-life care for their care recipient or at least there was an assigned surrogate. Although limited, these findings reflect more end-of-life planning in this population than previous studies reported and could improve the quality of end-of-life outcomes in this population by giving health-care providers increased understanding of African American end-of-life planning preferences. This may, in turn, help the providers to inform and educate these care recipients and their family caregivers.